Assessment of hypoxic subvolumes in laryngeal cancer with 18F-fluoroazomycinarabinoside (18F-FAZA)-PET/CT scanning and immunohistochemistry. Issue 1 (October 2015) - Bruine de Bruin, Leonie; Bollineni, Vikram R.; Wachters, Jan E.; Schuuring, Ed; van Hemel, Bettien M.; van der Wal, Jacqueline E.; Slagter-Menkema, Lorian; de Bock, Geertruida H.; Steenbakkers, Roel J.H.M.; Langendijk, Johannes A.; Pruim, Jan; van der Laan, Bernard F.A.M.; et al.
Abstract Background and purpose 18F-fluoroazomycinarabinoside (18F-FAZA) is a promising hypoxia radiopharmaceutical agent with outstanding biokinetic parameters. We aimed to determine the accuracy of 18F-FAZA-PET/CT scan in detecting hypoxic regions within the tumor using immunohistochemical markers in a pilot study. Patients and methods Eleven patients with primary or recurrent laryngeal squamous cell carcinoma were indicated for total laryngectomy (TLE). Patients underwent 18F-FAZA-PET/CT scan before TLE. Hypoxic regions inside the laryngeal tumor were determined. After TLE, regions with high uptake on 18F-FAZA-PET scan were selected for immunohistochemical examination for exogenous (pimonidazole) and endogenous (HIF1α, CA-IX and GLUT-1) hypoxia markers. To assess the accuracy of 18F-FAZA-PET scanning, radiopharmacon accumulation was related with immunohistochemical expression of hypoxia markers. Results Inter- and intratumoral heterogeneity of tumor hypoxia was observed on 18F-FAZA-PET scan. Nine of the eleven tumors were hypoxic with 18F-FAZA-PET. Hypoxia could also be detected with pimonidazole, HIF1α, CA-IX and GLUT-1 expression in some tumors. No clear association was observed between 18F-FAZA uptake and hypoxia markers. Conclusions This pilot study could not prove the accuracy of 18F-FAZA-PET in determining hypoxic subvolumes in laryngeal cancer. Further study is required to investigate the benefit of 18F-FAZA-PET imaging in radiotherapy planning.